2005
DOI: 10.1016/j.orthres.2005.04.009.1100230631
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C attenuates acute ischaemia reperfusion injury in skeletal muscle

Abstract: Activated protein C (APC) is an endogenous anti-coagulant with anti-inflammatory properties. The purpose of the present study was to evaluate the effects of activated protein C in the setting of skeletal muscle ischaemia reperfusion injury (IRI). IRI was induced in rats by applying rubber bands above the levels of the greater trochanters bilaterally for a period of 2 h followed by 12 h reperfusion. Treatment groups received either equal volumes of normal saline or activated protein C prior to tourniquet releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Beneficial effects of activated protein C involve inhibition of diverse molecular mechanisms of inflammation and cellular damage, including those related to overt generation of circulating and locally produced proinflammatory mediators, the presence of activated leukocytes, and endothelial cell activation (14,15,26). In vitro experiments also revealed that activated protein C may exert inhibitory effects on reactive oxygen species generation and lipid peroxidation (29,30). Overall, experimental evidence supports a role of activated protein C in maintaining the integrity of the endothelium through both direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of activated protein C involve inhibition of diverse molecular mechanisms of inflammation and cellular damage, including those related to overt generation of circulating and locally produced proinflammatory mediators, the presence of activated leukocytes, and endothelial cell activation (14,15,26). In vitro experiments also revealed that activated protein C may exert inhibitory effects on reactive oxygen species generation and lipid peroxidation (29,30). Overall, experimental evidence supports a role of activated protein C in maintaining the integrity of the endothelium through both direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many medical treatment options such as recombinant human BCL2 protein, ethyl pyruvate, laser therapy, hydrogen sulfide, PJ 34, poloxamer 188, ketamine, recombinant human VEGF165 protein, activated protein C, adenosine A, bortezomib, MRS2693, hypertonic saline solution, cariporide, grape seed proanthocyanin extract, Wisconsin solution, ultrasound, erythropoietin, resveratrol, vitamin E, 12 amino acid peptides have been experimentally studied and all of them were reported to have positive effects at some degree. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] However, studies on all these agents remained experimental and these agents failed to find a place in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…APC administration has also been shown to reduce the oxidative damage and edema associated with skeletal muscle ischemia-reperfusion injury. 90 In a rat model of hind limb ischemia-reperfusion injury, Dillon et al showed reduced myeloperoxidase levels and protected electrical muscle activity in animals treated with intravenous APC. In addition, through a series of in vitro experiments, they demonstrated that human neutrophils treated with APC exhibited reduced CD18 expression and ROS generation.…”
Section: Apc and In Vivo Models Of Ischemia-reperfusion Injurymentioning
confidence: 99%
“…In addition, through a series of in vitro experiments, they demonstrated that human neutrophils treated with APC exhibited reduced CD18 expression and ROS generation. 90 Despite the evidence supporting the use of APC in several in vivo and in vitro models of ischemiareperfusion injury, there is little published regarding the clinical use of APC in microvascular surgery. Although the hind limb ischemia-reperfusion experiments of Dillon et al are particularly informative, no published studies to date have examined the use of APC in the prevention of ischemia-reperfusion injury in free or pedicled fasciocutaneous or musculocutaneous flap models.…”
Section: Apc and In Vivo Models Of Ischemia-reperfusion Injurymentioning
confidence: 99%
See 1 more Smart Citation